2017
DOI: 10.3847/1538-3881/aa5be4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the VVV Survey RR Lyrae Population across the Southern Galactic Plane

Abstract: Deep near-IR images from the VISTA Variables in the Vía Láctea (VVV) Survey were used to search for RR Lyrae stars in the Southern Galactic plane. A sizable sample of 404 RR Lyrae of type ab stars was identified across a thin slice of the fourth Galactic quadrant (295°< ℓ < 350°, −2°.24 < b < −1°.05). The sample's distance distribution exhibits a maximum density that occurs at the bulge tangent point, which implies that this primarily Oosterhoff type I population of RRab stars does not trace the bar delineated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 59 publications
5
31
0
Order By: Relevance
“…However, results from the Kolmogorov-Smirnov test suggests that the Oo I and II groups are drawn from the same distribution, with a p-value = 0.27. Overall neither of the groups seems to cluster at the position of the Galactic bar, which is in agreement with the previous studies done by Dékány et al (2013) and Minniti et al (2017) as well as seen in the study of the disk RR Lyrae stars by ). In addition, in the bottom panel of Fig.…”
Section: Oosterhoff Groups With Respect To the Galactic Barsupporting
confidence: 93%
See 1 more Smart Citation
“…However, results from the Kolmogorov-Smirnov test suggests that the Oo I and II groups are drawn from the same distribution, with a p-value = 0.27. Overall neither of the groups seems to cluster at the position of the Galactic bar, which is in agreement with the previous studies done by Dékány et al (2013) and Minniti et al (2017) as well as seen in the study of the disk RR Lyrae stars by ). In addition, in the bottom panel of Fig.…”
Section: Oosterhoff Groups With Respect To the Galactic Barsupporting
confidence: 93%
“…In the background and central region of the Galactic bulge we observe an increase of Oo II variables, which is probably an observational bias due to their higher brightness. We do not observe any spatial correlation with the Galactic bar for the aforementioned Oosterhoff groups, which is in agreement with Dékány et al (2013) and Minniti et al (2017) but in disagreement with Pietrukowicz et al (2015). One of the possible reasons for this discrepancy is a different treatment of extinction, and that our analysis, unlike that of Pietrukowicz et al, is partly based on near-infrared data.…”
Section: Discussionsupporting
confidence: 82%
“…The VISTA Variables in Vía Láctea (VVV) team conducted a near-infrared (NIR) K s -band multi-epoch survey of the Galactic bulge and southern disk. They found 404 RR Lyrae in the southern Galactic plane (Minniti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is given to old stars which are thought to be formed in the first galaxies. This is of particular interest, given the recent detections of old RR Lyrae stars in the bulge-halo ) and the disc-halo (Minniti et al 2017) regions by the VVV survey. Furthermore, Santucci et al (2015) and Carollo et al (2016) identified the so-called "ancient chronographic sphere (ACS)" in the inner region of the MW's stellar halo, which is claimed to be populated by stars older than 10 Gyr.…”
Section: Introductionmentioning
confidence: 99%
“…The Milky Way (MW) offers a unique perspective to test models of galaxy formation because stars can be individually observed and their properties, such as kinematics, dynamics, and chemical composition, can be more accurately derived in the four main stellar components: bulge, thin and thick discs and stellar haloes (see Bland-Hawthorn & Gerhard 2016, for a detailed discussion of the MW components). The copatricia.tissera@unab.cl existence of these components in the central region is now being explored in more detail as the result of larger and more precise observational data in the bulge (e.g., Gran et al 2016;Zoccali et al 2016), stellar halo (e.g., Santucci et al 2015;Carollo et al 2016;Helmi et al 2016) and the disc (e.g., Minniti et al 2017). …”
Section: Introductionmentioning
confidence: 99%